Calidad de vida del adulto mayor con hipertensión arterial atendidos en el Hospital General IESS Babahoyo, periodo mayo-agosto 2024. - Gavilanes Riascos, Nathaly Germania (2024)
Quality of life is a complex concept that encompasses the objective and subjective perspective, referring to the person's satisfaction with their daily lives. Quality of life is usually compromised in older adults with certain pathologies. Objective: Determine the quality of life of older adults with high blood pressure treated at the IESS Babahoyo General Hospital, period May-August 2024. Methodology: The study had a non-experimental design, quantitative modality, descriptive, field and transversal with a sample of 50 older adults with a diagnosis of arterial hypertension, the Whoqol-Bref Quality Scale was used as an instrument. Results: In terms of sociodemographic characteristics, they were 65 to 70 years old (40.0%), male sex (54.0%), married (44.0%), secondary educational level (54.0%), retired (80.0%) and rural residence (64.0%); The overall quality of life was average (50.0%) and according to the dimensions, medium level in physical health (50.0%), high level in psychological health (38.0%), low level in social relationships (66.0%), 0%) and medium level in environmental dimension (60.0%). Conclusion: Older adults with arterial hypertension treated at the IESS General Hospital of Babahoyo have an average perception of their quality of life.